Developing the methodology of colour gamut analysis and print quality evaluation for textile ink‐jet printing: Delphi method. (7th November 2017) - Ding, Yi; Parrillo‐Chapman, Lisa; Freeman, Harold S.
Abstract : This research used the Delphi method to investigate current colour gamut analysis methods, which is a critical component of colour management systems (CMS). Thirteen ink‐jet printing experts were interviewed to understand how they manage colour and their process for analysing and comparing colour gamut. A significant result of this study was the development of a four‐stage process model for colour gamut analysis and print quality evaluation for textile ink‐jet printing. The optimal process model was verified and approved by experts. This study uncovered an industry initiative toward the improvement of CMS for more accurate colour matching, a need to stabilise variables in the manufacturing process, and a need to standardise related tests and evaluations. The study also revealed new CMS software and technologies developed for ink formulation and pre‐/post‐treatment methods to facilitate high quality production in textile ink‐jet printing.